How to control your anxiety before it controls you - Ellis, Albert, 1913-2007 (Citadel Press Books, 2016)
"From social anxiety to phobias to post-traumatic stress disorder, sources of anxiety in daily life are numerous, and can have a powerful impact on your future. By following hte rules of Rational Emotive Behavior Therapy (REBT), created by world renowned therapist Dr. Albert Ellis, you can stop anxiety in its tracks if you will admit this important fact: Things and people do not make you anxious. You do. Your unrealistic expectations produce your needless anxiety. Yet not all anxiety is needless... Healthy anxiety can ward off dangers and make you aware of negative things that you can change. Unhealthy anxiety inhibits you from enjoying everyday activities and relationships, causes you to perform poorly, and blocks your creativity. Using the easy-to-master, proven precepts of REBT, this classic book not only helps you distinguish between healthy and unhealthy anxiety, but teaches you how to: Understand and dispute the irrational beliefs that make you anxious; Use a variety of exercises, including rational coping self-statements, reframing, problem-solving methods, and Unconditional Self-Acceptance (USA), to control your anxiety; Apply over 200 maxims to control your anxious thinking as well as your bodily reactions to anxiety... and much more, including examples from dozens of cases Dr. Ellis treated successfully"--Back cover,